A new genus and species of Oemini (Coleoptera, Cerambycidae) from Sichuan Province, western China - Niisato, Tatsuya; Liu, Bin (Zootaxa, 2019)
A new genus and species of Oemini (Oemina), Sichuanortia zhouchaoi, is described from Sichuan Province, western China. The new genus is similar to the genus Oemospila Gahan, 1906 in general appearance, but it is clearly distinguished by the deeply furrowed gula instead of the relatively smooth gula as in the latter.